Nutrient analysis of sorghum dried distillers grains with solubles from ethanol plants located in the western plains region - Sotak, K.M.; Goodband, Robert D.; Tokach, Michael D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Samples of sorghum dried distillers grains with solubles (DDGS) were collected and analyzed to establish a nutrient database and evaluate the quality and consistency between and within samples taken from 5 ethanol plants in the Western Plains region. Four plants were located in Kansas and 1 in Texas. A total of 21 samples were collected, with 4 plants contributing 4 samples each and 1 plant contributing 5 samples from different manufacturing lots of DDGS. Each sample was analyzed for amino acids, DM, CP, crude fiber, crude fat, ash, NDF, ADF, Ca, P, trace minerals, GE, and starch. In addition, DE, ME, and NE were calculated from the nutrient analysis. Of the 5 plants, 3 produced pure sorghum DDGS samples while 2 produced mixed sorghum and corn DDGS samples, with sorghum representing 60 or 70% of the DDGS. For the pure sorghum DDGS, the overall sample average means for each nutrient on a DM basis were: DM (89.5%), CP (34.2%), crude fat (10.5%), ash (4.4%), NFE (40.3%), crude fiber (10.6%), ADF (26.4%), NDF (35.1%), starch (4.3%), calculated DE (1,560 kcal/lb), calculated ME (1,454 kcal/lb), calculated NE (919 kcal/lb), Ile (1.37%), Leu (3.84%), Lys (0.88%), Met (0.55%), Thr (1.04%), Trp (0.26%), Val (1.67%), Ca (0.01%), and P (0.72%). The mixed DDGS samples’ means were generally similar to the pure sorghum DDGS nutrient analysis values. Results of these analyses can be used by nutritionists to better utilize sorghum DDGS in swine diets.
Keywords: Swine; Dried distillers grains with solubles; Nutrient analysis; Sorghum